Garnering Partnerships to Bridge Gaps Among Mental Health, Health Care, and Public Health - Elsie Freeman, MD, MPH; Letitia Presley-Cantrell, PhD, MEd; Valerie J. Edwards, PhD; Sharrice White-Cooper, MPH; Kenneth S. Thompson, MD; Stephanie Sturgis, MPH; Janet B. Croft, PhD (Centers for Disease Control and Prevention, 2010)
Integrating mental health and public health chronic disease programs requires partnerships at all government levels. Four examples illustrate this approach: 1) a federal partnership to implement mental health and mental illness modules in the Behavioral Risk Factor Surveillance System; 2) a state partnership to improve diabetes health outcomes for people with mental illness; 3) a community-level example of a partnership with local aging and disability agencies to modify a home health service to reduce depression and improve quality of life among isolated, chronically ill seniors; and 4) a second community-level example of a partnership to promote depression screening and management and secure coverage in primary care settings. Integration of mental health and chronic disease public health programs is a challenging but essential and achievable task in protecting Americans' health.